2012
DOI: 10.1016/j.jcrs.2011.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative performance and postoperative outcome comparison of longitudinal, torsional, and transversal phacoemulsification machines

Abstract: All 3 phacoemulsification machines were effective with no significant intraoperative complications. The torsional machine outperformed the transversal and longitudinal machines, with a lower mean needle time, less chatter, and improved followability. This corresponded to less corneal edema 1 day postoperatively and better visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 29 publications
2
41
0
8
Order By: Relevance
“…The difference between the groups in this minimal level of corneal edema did not reach statistical significance. However, Christakis and Braga-Mele5 found that torsional technology yielded less central corneal edema than the transversal and longitudinal technologies, corresponding to a smaller increase in the mean corneal thickness (torsional, 5%; transversal, 10%; longitudinal, 12%). One of the main factors accounting for this discrepancy with our findings may be the difference in the nuclear cataract grade, which was NC 2.0 ± 0.8 in Christakis and Braga-Mele’s study 5…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The difference between the groups in this minimal level of corneal edema did not reach statistical significance. However, Christakis and Braga-Mele5 found that torsional technology yielded less central corneal edema than the transversal and longitudinal technologies, corresponding to a smaller increase in the mean corneal thickness (torsional, 5%; transversal, 10%; longitudinal, 12%). One of the main factors accounting for this discrepancy with our findings may be the difference in the nuclear cataract grade, which was NC 2.0 ± 0.8 in Christakis and Braga-Mele’s study 5…”
Section: Discussionmentioning
confidence: 96%
“…Torsional and transversal phaco modes are the results of these technological advances. Several studies have confirmed and reported the superiority of torsional phaco over longitudinal phaco in terms of needle time, chatter, followability, corneal edema, and corneal endothelium 1,5,712,19,20. However, to date, only one study has compared longitudinal, torsional, and transversal phaco 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataract surgery is improving in a rapid pace. Surgical parameters such as phacoemusification time, used amount of ultrasound energy and size of incisions were reduced to allow a minimal invasive procedure . Additionally, advances of the intraocular lens (IOL) design procure a better visual outcome and a safer surgery .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, remarkable advances have been made in phacoemulsifier (phaco) devices for use in cataract surgery, enabling the insertion of ultrasound (US) tips and sleeves via microincisions, improving anterior chamber stability, and increasing surgical efficiency even with low phaco power output during nuclear phacoemulsification [1][2][3][4]. The Infiniti ® Vision System platform (Alcon Laboratories, Inc., Fort Worth, TX, USA) (hereinafter Infiniti) enables torsional phacoemulsification with the Ozil ® handpiece in addition to conventional longitudinal phacoemulsification [5,6].…”
Section: Introductionmentioning
confidence: 99%